Relational aesthetics through Islamic Calligraphy Workshop/ Mumtaz Mokhtar ... [et al.] - Mokhtar, Mumtaz; WMD, Wan Samiati Andriana; Sabri, Nik Syahida; Hamidon, Nor Azlin (Universiti Teknologi MARA, Perak, 2023)
Malay calligraphy is known as Jawi and is a form of writing that is less popular compared to other modern writings such as those already listed in the font selection on students' computers. Therefore, Jawi workshop was held at the Fine Arts Studies, College of Creative Arts, MARA University of Technology for 77 students of the 3rd semester who enrolled Form and Soul course. The first objective is to introduce and further strengthen the writing skills of traditional Malay writing with the theme of 'knowledge'. Secondly, the whole activity of the workshop is to establish relational aesthetic form where the facilitator and students interact directly during the demonstration and practice throughout the workshop. The theoretical concept of knowledge involved the theme, selection of phrases related to knowledge, transformation of Roman writing into Jawi spelling, and identifying calligraphy styles. The students also been introduced to several artists who applied Jawi elements in contemporary artworks. Mumtaz Caligraphy set helps the creations of beautiful Jawi calligraphy letters, the arrangement of the lines, the decoration and composition of the letters and also the layout through the assistance of Associate Professor Dr Nor Azlin Hamidon and her teammates. Relational aesthetics artwork successfully unites traditional elements and contemporary forms into a meaningful artistic creation and beneficial art for society.